Exercise participation and health promotion in active seniors in aging societies: keys to successful aging - Choi, Soo-Jin; Zheng, Fang; Lee, Seung-Man (Frontiers in Public Health, 2025)
IntroductionAs populations age worldwide, promoting health and autonomy in later life has become a shared policy imperative. However, little is known about how concurrent lifestyle behaviors among physically active seniors influence their perceived health outcomes.MethodsUsing data from the 2023 National Survey on Physical Activity, this study analyzed 1,729 physically active older adults in South Korea. Descriptive statistics, independent t-tests, and multiple regression analyses were conducted to examine the associations between exercise participation, co-occurring health behaviors, and self-reported gains related to daily functioning and healthcare costs.ResultsRegular diet management and nutritional supplementation, along with abstinence from alcohol and smoking, were consistently associated with greater perceived assistance in daily activities and reduced healthcare costs. In contrast, regular physical activity and adequate rest showed no significant associations with most positive outcomes, except for a modest link with reduced healthcare costs. Self-reported gains—especially in daily activity assistance and cost reduction—were positively associated with perceived health and fitness status.DiscussionAmong already active seniors, integrated lifestyle strategies emphasizing dietary management and substance abstinence appear to yield more tangible benefits than exercise alone. Policy and practice should therefore complement exercise promotion with nutrition support and cessation programs, leveraging community sports-club infrastructures to sustain these behaviors in aging societies.